Adsorption Property of CS(2) and COF(2) on Nitrogen-Doped Anatase TiO(2)(101) Surfaces: A DFT Study - Cao, Zhengqin (ACS Omega, 2020)
[Image: see text] SF(6) has been utilized widely as an electrical insulation medium because of its excellent arc extinguishing performance and insulation characteristics. In this paper, the adsorption property of two kinds of key SF(6) carbon-containing decomposition components (CS(2) and COF(2)) on nitrogen-doped anatase TiO(2)(101) (N–TiO(2)) surfaces was simulated and analyzed based on density functional theory. The results demonstrated that N–TiO(2) shows good gas sensitivity toward CS(2) with the increase of conductivity but is insensitive toward COF(2). In addition, the gas-sensing property of CS(2) on N–TiO(2) is stronger than that of COF(2). This work provides the theoretical information on such a gas-sensitive material for key SF(6) carbon-containing decomposition components, supporting its utilization as a chemical sensor applied in condition monitoring and defect diagnosis in SF(6) gas-insulated equipment based on decomposition component analysis.